Thysanolaena maxima (roxb.) kuntze: a therapeutically less explored plant from northeastern India - Safal Sharma; Bibhas Pandit; Sushilta Pradhan; Jyochhana Mohanty (Journal of Applied Pharmaceutical Research, 2022)
Thysanolaena maxima is a member of the Poaceae family of medicinal plants, and it is used to cure a variety of ailments, including boils, vomiting, stomach disorders, and infectious diseases like tuberculosis. Thysanolaena maxima has been found to possess a variety of chemicals, including terpenoids, polysaccharides, tannins, flavonoids, saponins, glycosides, phenols, and steroids. The current mini-review analyses its pharmacological profile, chemical components, and phytochemistry, with an emphasis on, cytotoxic, antioxidant and antimicrobial properties, in order to better assess the plant's medicinal potential. Traditional and modern medicine, as well as possible herbal therapy for a number of ailments, have a lot of potential for Thysanolaena maxima. Its active ingredients and pharmacological activities is yet to be thoroughly researched. This brief review has offered up-to-date work on Thysanolaena maxima's phtyochemical and other information, which will serve as a reference for future research